?-AMILASE INHIBITORY ACTIVITY OF SOME MEDICINAL PLANTS AND ISOLATION OF ACTIVE COMPOUND FROM SELECTED PLANT (FICUS RELIGIOSA L.) - Jaizzur Rija'i, Akhmad
Diabetes and its complication was major causes of death in most countries compared HIV/AIDS, tuberculosis and malaria. One approach in the treatment of diabetes is by slowing down the glucose absorption in the gastrointestinal tract, its can be achieved by inhibition of hydrolizing enzymes such as ?-amylase so the absorption of glucose becomes slow. This research aim was to determine the ?- amylase inhibitor activity from aqueous extract of the plant and from the selected plants the active compound was isolated. Extraction was done by reflux method using aquadest as a solvent. Extracts were obtained by freeze drying and tested for ?-amylase inhibitory activities. Percent inhibition value of bodhi leaves aqueous extract at concentration 500 µg/mL was 72,43% ± 4,23 and it was selected to be fractionated by liquid-liquid extraction using n-hexane and ethyl acetate. Extract and fractions of bodhi leaves were tested for ?-amylase inhibitory activities compared with acarbose. The IC50 value of aqueous extract, n-hexane, ethyl acetate, water fraction of bodhi leaves and acarbose as reference were 282,53; 759,93; 459,58; 345,64; and 3,42 µg/mL, respectively. The ethyl acetate fraction was separated using column chromatography (CC) with isochratic elution (chloroform-acetone). Subfraction 122 and 123 were further separated using sentrifugal thin layer chromatography with gradient elution from n-hexane-ethyl acetate-methanol to obtain fraction containing compund X. It was purified using centrifugal thin layer chromatography with isochratic elution (ethyl acetatechloroform-acetone-methanol) to obtain compound X. It characterized by specific spraying reagents and was tested for ?-amylase inhibitory activities. Based on the result of charactersization by specific spray reagent that compund X was a class of coumarin and percent inhibition value of compound X at concentration 500 µg/mL was 57,34% ± 1,37.